FRAGMENTED REALITIES: A COMPARATIVE STUDY OF PARTISAN FRAMING IN LEBANESE TELEVISION TALK SHOWS - Awarki, Zeinab (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Under the conditions of extreme plurality of political and ideological positions in the media space, the Lebanese television system also becomes not a single public space but a producer of parallel realities. The phenomenon of Echo Chamber that is discussed in this paper refers to Lebanese talk shows that is to say, the talk shows of MTV, Al-Jadeed, and Al-Manar and how the perceptions of the people regarding systemic state failure are disaggregated through partisan framing. The analysis of Interpretive Polarization of the causes of the national crisis based on comparative framing analysis and the survey of 200 Lebanese young people is the focus of the study. The results express that on one hand, there is an actual existence of a nominal "Public Agenda" and on the other hand, the causal attribution of the economic collapse was diametrically opposite along the channel audiences (correlation=0.67correlation=0.67). Whereas readers of MTV place emphasis on inner-institutional breakdown, viewers to Al-Manar emphasize outer-geopolitical pressures, and those of Al-Jadeed place emphasis on populist anti-establishment. The analysis summarizes that media addiction in Lebanon strengthens the social divisions that already exist in the country such that it turns a unified national crisis into unraveled partisan discourses that are not susceptible to a civic identity solution.